Language Error Found on Social Media of Indonesian Celebrities - randy saputra; dian mukhlisa (English Language, Linguistics, Literature, And Education Journal, 2022)
This thesis discusses the kinds of language error found on social media of Indonesian celebrities and the factors that affect the language of Indonesian celebrities. This study is designed to find out the kinds of language error is made Indonesian celebrity used in communicating on social media and to find out the factors that influence the Indonesian celebrity language. This research uses qualitative and descriptive research method. The object of this research is Indonesian celebrities. And there are 10 Indonesia celebrties who were sampled in this study, and the researcher took 3 captions from each celebrity. The research data was taken from screenshots of Indonesian celebrity captions and videos. The way of collecting data is by using documentation. The data are classified according to the kinds of language error and factors that affect language according to Ellis & Brown's theory. In this study, the researcher found that there were 28 data that writer got from social media of Indonesian celebrities, such as Instagram and YouTube. From the 3 kinds of language error according to Ellis' theory, the researcher got 7 data from omission, the researcher got 14 data from misinformation, 1 data from misordering, and 6 data from combination of 2 kinds of error. Then the language error factor, the researcher found 6 data from the interlingual factor, 14 data from the intralingual factor, 3 data from the context of learning factor, and 5 data from combination of 2 factors of error.